2023
DOI: 10.1039/d3fo03568a
|View full text |Cite
|
Sign up to set email alerts
|

The protective effects of beta-mangostin against sodium iodate-induced retinal ROS-mediated apoptosis through MEK/ERK and p53 signaling pathways

Yuan-Yen Chang,
Meilin Wang,
Jui-Hsuan Yeh
et al.

Abstract: Previous studies have indicated that NaIO3 induces intracellular reactive oxygen species (ROS) production and has been used as a model for age-related macular degeneration (AMD) due to the selective retinal pigment epithelium (RPE) cell damage it induces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…To understand the protective mechanisms, we observed the protection of LUWE using NaIO 3 -induced ARPE-19 cells based on previous studies [20,31,66]. We observed that 2.5 mg/mL LUWE can effectively suppress NaIO 3 -induced ARPE-19 cell death (Figure 3B).…”
Section: Discussionmentioning
confidence: 85%
“…To understand the protective mechanisms, we observed the protection of LUWE using NaIO 3 -induced ARPE-19 cells based on previous studies [20,31,66]. We observed that 2.5 mg/mL LUWE can effectively suppress NaIO 3 -induced ARPE-19 cell death (Figure 3B).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, P53 is involved in regulating cellular metabolism, influencing the progression of eye diseases such as diabetic retinopathy by affecting blood sugar balance and fatty acid oxidation ( 64 ). The activity of P53 is also linked with neuroprotection in age-related macular degeneration and glaucoma ( 65 ). In these conditions, it fosters the expression of stress-resistant molecules to shield retinal neurons from degeneration.…”
Section: Characteristics Of Ferroptosismentioning
confidence: 99%